2018
DOI: 10.1136/bmjopen-2018-022583
|View full text |Cite
|
Sign up to set email alerts
|

Stillbirth among women in nine states in India: rate and risk factors in study of 886,505 women from the annual health survey

Abstract: ObjectivesTo assess the rate of stillbirth and associated risk factors across nine states in India.DesignSecondary analysis of cross-sectional data from the Indian Annual Health Survey (2010–2013).SettingNine states in India: Madhya Pradesh, Chhattisgarh, Rajasthan, Uttarakhand, Jharkhand, Odisha, Bihar, Assam and Uttar Pradesh.Participants886 505 women, aged 15–49 years.Main outcome measuresStillbirth rate with 95% CI. Adjusted OR to examine the associations between stillbirth and (1) socioeconomic, behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 26 publications
4
48
4
Order By: Relevance
“…Thus, aforementioned studies were conducted in referral hospitals which have better obstetric care facilities and skilled health workforce; whereas our study setting was a general hospital with fewer obstetricians and majority of cases were referred from peripheral primary health care units with poor facilities, which provide obstetric services for a predominantly rural population. The proportion of stillbirths in our nding was also higher than the global estimates of stillbirth for Ethiopia (25,26), and other studies from developing countries such as Bangladeshi (27) and India (28). This variation could be partly explained by differences in study settings and methods because the present study was a hospital based study unlike other community based studies from developing countries.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Thus, aforementioned studies were conducted in referral hospitals which have better obstetric care facilities and skilled health workforce; whereas our study setting was a general hospital with fewer obstetricians and majority of cases were referred from peripheral primary health care units with poor facilities, which provide obstetric services for a predominantly rural population. The proportion of stillbirths in our nding was also higher than the global estimates of stillbirth for Ethiopia (25,26), and other studies from developing countries such as Bangladeshi (27) and India (28). This variation could be partly explained by differences in study settings and methods because the present study was a hospital based study unlike other community based studies from developing countries.…”
Section: Discussioncontrasting
confidence: 54%
“…Mothers in labour are often admitted and managed in the maternity ward of the hospital. Majority of mothers in labour are referred from the neighboring district hospitals and health centers for various obstetric and medical reasons (28).The total number of deliveries in one year period (from August 1, 2015-July 30, 2016) in the hospital was reported to be 3000.…”
Section: Study Settingmentioning
confidence: 99%
“…The AHS is a population-based household survey in which self-reported data on maternal and child health, demographics, birth and access to health and family planning services were collected from 4.3 million households in nine less developed states of India (Bihar, Chhattisgarh, Jharkhand, Madhya Pradesh, Odisha, Rajasthan, Uttar Pradesh, Uttarakhand and Assam), representing 50% of the country’s population, 61% of births and 62% of maternal deaths. 15 16 The AHS used a stratified simple random sampling (without replacement) to obtain a sample that was representative of and proportional to the size of the selected villages. Survey weights were developed to account for the sampling method.…”
Section: Methodsmentioning
confidence: 99%
“…All women who provided information on their pregnancy (91.3% most recent pregnancy and 8.7% on a previous pregnancy) were included. As in a previous study using the same dataset, women who had an abortion after 28 weeks were excluded as these were most likely to be stillbirths (according to the WHO definition for stillbirth) 15. A total of 1 876 462 women who reported being pregnant during the reference period 2007–2011 were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…43,64 A meta-analysis of risk factors in 886,505 women from nine states of India showed that tobacco chewing women (% of total) had higher odds of having stillbirth (OR: 1.1; 95% confidence interval [CI]: 1.02-1.21) after excluding other confounding factors. 65 Lessons learned from epidemiological and experimental animal model studies confirm these observations. 66 More than one-quarter of the risk of death due to SIDS is attributable to smoking during pregnancy and exposure to SHS, particularly in the home.…”
Section: Perinatal Mortality and Sudden Infant Death Syndromementioning
confidence: 80%